Comparison of Horizontal and Vertical Resolvable Resolution Between Repetitive Multi-Beam Surveys Using Different Kinematic GNSS Methods - McHugh, Christopher R.; Church, Ian; Kim, Min; Maggio (USA), David (The International Hydrographic Review, 2015)
Ellipsoid referenced surveying is quickly becoming the standard in hydrographic surveying. Traditionally tidal measurements were used to reduce soundings down to the survey datum. With Kinematic Global Navigation Satellite System (GNSS) techniques currently providing sub-decimeter level precision, in-situ tide measurements are no longer required for vertical referencing. This places a heavy dependence on GNSS techniques to consistently provide accurate positioning in the horizontal and vertical with low uncertainty. Hydrographers need to know which GNSS technique yields the best solution and if that method works in all conditions. The development of Real Time Networks (RTN) allow for a triangulated Virtual Reference Station (VRS) to be established anywhere in the survey area, eliminating the need for a physical base station set up over a benchmark. This project compares the differences in accuracy and uncertainty between RTN based VRS corrections, Post Processed Kinematic (PPK), Precise Point Positioning (PPP), and Real Time Kinematic (RTK) solutions. Repetitive overlapping multi-beam surveys were completed at one survey location on different days to assess the repeatability of ellipsoid referenced surveying.